2008
DOI: 10.1152/ajprenal.90315.2008
|View full text |Cite
|
Sign up to set email alerts
|

Urotheliogenic modulation of intrinsic activity in spinal cord-transected rat bladders: role of mucosal muscarinic receptors

Abstract: We examined the modulation of intrinsic (i.e., spontaneous) detrusor contractions by the urothelium and the lamina propria through optical mapping approaches. Normal adult and spinal cord-transected (SCT) rat bladders were stained with Ca2+- and voltage-sensitive dyes, and optical activity generated from intrinsic contractions was mapped from the mucosal surface of whole bladder sheets. Both normal adult and SCT rat bladders displayed intrinsic contractions, where normal bladders showed low-amplitude, high-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 55 publications
4
66
0
Order By: Relevance
“…32 In addition, in pathological conditions including cancer, an altered sensitivity of tumor cells to muscarinic receptors has been described. 33,34 Both these aforementioned explanations need further experiments to elucidate the biological function of M2 muscarinic receptors in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, in pathological conditions including cancer, an altered sensitivity of tumor cells to muscarinic receptors has been described. 33,34 Both these aforementioned explanations need further experiments to elucidate the biological function of M2 muscarinic receptors in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The ICs in the LP and within the detrusor may serve different functions. Available evidence suggests that the LP ICs may constitute a structural and functional link between urothelial cells and sensory nerves and/or between urothelial cells and detrusor smooth muscle cells (106,142,204). Moreover, these cells might be involved in the pathophysiology of urinary tract disorders (see below).…”
Section: Interstitial Cells/myofibroblastsmentioning
confidence: 99%
“…The physiological significance of what appears to be a cholinergic signaling system in the mucosa is unclear. Ikeda and Kanai (140,142) suggested that muscarinic receptors within the mucosa were involved in urotheliogenic signaling, enhancing intrinsic detrusor contractions. Isolated strips of porcine urothelium with lamina propria were shown to exhibit spontaneous contractile activity that was increased by stretch.…”
Section: Cholinergic Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 There is increasing evidence for the functional modulation by non-neuronal sources of transmitters in the bladder. For example, it has been shown that many factors including ACh 19 , ATP 20 , NO 21 can be released from the bladder urothelium. It is postulated that these non-neuronal sources of neurotransmitters interact with near-by tissues in the suburothelial layer to modulate afferent activity to control bladder function.…”
Section: Discussionmentioning
confidence: 99%